Design of a processing plant for low-methoxyl pectin (LMP) from tambis (Syzygium samarangense) - Frial, Caressa Marie Drilon (Miagao, Iloilo, Philippines University of the Philippines School of Science and Technology, 2012)
A pectin producing plant, of about 0.7 hectares, will be put in Bislig City, Surigao del Sur.
Sotech thesis.
Keywords: Pectin; Tambis (Syzygium samarangense).